A Review of Employee Innovation Behavior - Wei, Suting; Tang, Yuan (International Journal of Global Economics and Management, 2025)
Firstly, by tracing and combing the research literature related to employee innovative behavior, this paper condenses the employee innovative behavior based on the two dimensions of formation mechanism and influencing factors, and outlines the definition and formation stages of employee innovative behavior. Then this paper clarifies the influencing factors of employee innovative behavior from the individual, organizational and social dimensions, and finally summarizes the research reflections and puts forward some future research suggestions for the existing research limitations.